Prioritizing marine invasive alien species in the European Union through horizon scanning. Issue 4 (7th March 2020) - Tsiamis, Konstantinos; Azzurro, Ernesto; Bariche, Michel; Çinar, Melih E.; Crocetta, Fabio; De Clerck, Olivier; Galil, Bella; Gómez, Fernando; Hoffman, Razy; Jensen, Kathe R.; Kamburska, Lyudmila; Langeneck, Joachim; et al.
Abstract: The disproportionately low presence of marine species in the list of invasive alien species (IAS) of Union concern of the European Union (EU) Regulation 1143/2014 does not fully acknowledge the threat they pose to the EU marine environment. In this study, the first EU‐scale Horizon Scanning (HS) focusing on marine alien species was performed, aiming to deliver a ranked list of species that should be of high priority for risk assessment (Article 5 of the EU IAS Regulation). Species absent from or with a limited distribution in EU marine waters were targeted. In total, 363 alien species were initially screened for HS by a panel of experts, including a broad range of taxonomic groups. Species were scored for their likelihood of arrival, establishment, spread, and impact in EU waters. A consensus workshop ranked 267 species, including a subset of 26 prioritized species. These species are considered to be mainly introduced by shipping (fouling and ballast water), via the Suez Canal, and aquaculture activities. The 26 priority species were also scrutinized in terms of feasibility of their management; 18 of them were suggested for performing risk assessments on the basis of the EU IAS Regulation. Since biological invasions are dynamic and connected with accelerated globalization and diversified human activities, we recommend HS to be repeated periodically to review the species already listed and assess new ones.